Α DISEASE OF TURKEY CHICKEN DUE TO ARIZONA ARIZONAE - ΒΟΓΙΑΖΑΣ, Δ.; ΔΕΣΠΟΤΟΠΟΥΛΟΣ, Α.; ΜΑΓΚΟΥΤΑ, Π. (Journal of the Hellenic Veterinary Medical Society, 1973)
Many deaths of turkey chicken aged 1—20 days, as well as cases of turkey eggs not opened after the normal period of incubation or lethal chickens from incubated and opened eggs, led to the isolation of Arizona Arizona e. The clinical symptoms are described as well as the autopsy findings and the applied treatment which was consisting of the administration in the drinking water for 5—6 days one of the antibiotics to which the isolated strain was sensitive (Chloramphenicol or Neomycin)· This treatment gave a slight only decrease of morbidity and mortality.